Elasticity and urban vacancy: A longitudinal comparison of U.S. cities. (October 2016) - Newman, Galen; Gu, Donghwan; Kim, Jun-Hyun; Bowman, Ann O''.M.; Li, Wei
Abstract: The effects of urban expansion and population change on vacant land patterns are not fully understood. While the majority of previous research documents that depopulation can result in increased vacant urban areas, there are conflicting findings in regards to the effects of urban expansion. What remains unclear is whether higher urban elasticity (expansion in size) contributes to increases in urban vacancies, or the inverse. While elastic cities extend their boundaries and develop outwardly, inelastic cities contract or stay the same in size and utilize infill development. This research sought to determine if urban elasticity plays a significant role in contributing to urban vacancy increases through an exploratory, quasi-experimental longitudinal analysis of vacant address data from 40 U.S. cities of over 100, 000 persons from 2000 to 2010. We compared the top 20 elastic (boundaries expanded the most) and inelastic (boundaries contracted the most) cities. A fixed effects panel model was developed to observe changes over time and differences in total, residential, and business land uses. Results indicate that aggressive urban expansion can contribute to increased urban vacancies, specifically in reference to residential land uses. This finding clarifies what had heretofore been a murky aspect of the urban studies literature. Highlights: It is unclear whether urban elasticity can significantly contribute to increased vacancies. Fixed effect panel models can be used to observe changes and differences in vacancies by land uses. Aggressive expansion can contribute to urban vacancies, specifically in residential land uses. Growing and shrinking cites should be wary of increases in urban vacancies.